Diatom population and nutrient survey in the Mississippi River at Lock 7 and Lock 8 - Ozburn, Clement (My University, 1969)
The purpose of this study is twofold: (1) to obtain information which may be used to determine to what extent diatoms can be used as water quality indicators; (2) to supplement baseline data on annual plankton standing crops of the upper Mississippi River. This survey began 3 October, 1967 and continued through 30 September, 1968. Three samples were taken every two weeks: one in Pool 7 above Lock and Dam No. 7, one in the channel at Lock and Dam No. 7, and one in the channel at Lock and Dam No. 8. A water nutrient analysis was done in addition to the diatom survey. Sixty seven species of diatoms are identified in this survey. The data includes only the ten species which made up 5% or more of each sample. Species domination, timing of annual maximum standing crops, and per cent occurrence-per cent volume relationships are compared to the Department of Health, Education and Welfare's Water Pollution Surveillance System reports (1957-1967). Correlations of standing crop and physiochemical factors are discussed.
Keywords: Water quality -- Mississippi River; Diatoms -- Mississippi River